An intermediate point obstacle avoidance algorithm for serial robot. (May 2018) - Chen, Zhuo; Su, Weihua; Li, Bin; Deng, Baosong; Wu, Hang; Liu, Baozhen
The trajectory planning and obstacle avoidance of serial robot is an important area of research and efficient optimization algorithms are needed. This article proposes an intermediate point obstacle avoidance algorithm to ensure smooth trajectory and efficient movement during the obstacle avoidance process. Using the intermediate point obstacle avoidance algorithm, the robotic arm can steer obstacle around with the minimum joint space variations and the shortest end motion trajectory. We also design a novel collision detection strategy and fitness evaluation function based on genetic algorithm to optimize the intermediate point parameters. In order to evaluate the performance of the intermediate point obstacle avoidance algorithm, we have conducted three typical experiments: single obstacle, multiple obstacles, and no obstacle. The experimental results demonstrate that the proposed method can not only effectively realize the obstacle avoidance, but also efficiently improve the movement performance of the robotic arm.